Novel myeloma patient-derived xenograft models unveil the potency of anlotinib to overcome bortezomib resistance - Yue, Yanhua; Cao, Yang; Mao, Xunyuan; Wang, Fei; Fan, Peng; Qian, Long; Guo, Shuxin; Li, Feng; Guo, Yanting; Chen, Tongbing; Lin, Yan; Dong, Weimin; et al. (Frontiers in Oncology, 2022)
Multiple myeloma (MM) remains a common hematologic malignancy with a 10-year survival rate below 50%, which is largely due to disease relapse and resistance. The lack of a simple and practical approach to establish myeloma patient-derived xenograft (PDX) hampers translational myeloma research. Here, we successfully developed myeloma PDXs by subcutaneous inoculation of primary mononuclear cells from MM patients following series tumor tissue transplantations. Newly established myeloma PDXs retained essential cellular features of MM and recapitulated their original drug sensitivities as seen in the clinic. Notably, anlotinib therapy significantly suppressed the growth of myeloma PDXs even in bortezomib-resistant model. Anlotinib treatments polarized tumor-associated macrophages from an M2- to an M1-like phenotype, decreased tumor vascular function, and accelerated cell apoptosis in myeloma PDXs. Our preclinical work not only unveiled the potency of anlotinib to overcome bortezomib resistance, but also provided a more practical way to establish MM PDX to facilitate myeloma research.